The Concept of China’s Peaceful Rise and Offensive Realism - Araszkiewicz, Adam (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2021)
This article aims at adressing several research issues. Firstly, to present offensive realism as a proper research tool to analyse US-China rivalry. Secondly, the author discusses the theory of “China’s peaceful rise” and I argues that it smoothly overlapped with the US strategy of liberal hegemony. Thirdly, He presents and defends the argument that China does not rise peacefully. Fourthly, the author claims that China wants to became a regional hegemon in South-East Asia and the USA according to offensive realism cannot let it happen. Last but not least the author considers the arguments that are frequently used to support the theory of “China’s peaceful rise” and explains why they fail to depict the current and predict the future nature of US-China relations. In this article the author employed the following research methods: historical, descriptive and decision making methods.

Ten artykuł ma na celu odniesienie się do kilku zagadnień badawczych. Po pierwsze, przedstawić ofensywny realizm jako odpowiednie narzędzie badawcze do analizy rywalizacji USA-Chiny. Po drugie, autor omawia teorię „pokojowego wzrostu Chin” i argumentuje, iż była ona w zasadniczej mierze kompatybilna z amerykańską strategią liberalnej hegemonii. Po trzecie, autor przedstawia i broni argumentu, iż rozwój Chin nie odbywa się pokojowo. Po czwarte, autor twierdzi, że Chiny chcą zostać regionalnym hegemonem w Azji Południowo-Wschodniej, a USA zgodnie z ofensywnym realizmem nie mogą na to pozwolić. Wreszcie autor rozważa argumenty, które są często używane na poparcie teorii „pokojowego wzrostu Chin” i wyjaśnia, dlaczego nie oddają one aktualnego i nie przewidują przyszłego charakteru stosunków USA-Chiny. W artykule zastosowano następujące metody badawcze: historyczną, opisową i decyzyjną.
Koncepcja pokojowego wzrostu Chin według paradygmatu realistycznego
Keywords: USA; China; China’s peaceful rise; offensive realism; USA; Chiny; pokojowy wzrost Chin; ofensywny realizm